Revisiting visual accessibility with non-textual content: challenges and solutions for human-computer interaction - Vargas, Pablo Nunes; Trevisan, Daniela Gorski (Anais do Simpósio Brasileiro sobre Fatores Humanos em Sistemas Computacionais (IHC), 2024)
Content like complex graphics, diagrams, and infographics poses significant challenges in terms of description, comprehension, and communication for individuals with visual limitations. Addressing these challenges requires innovative solutions and a deep understanding of the needs of visually impaired individuals. In this context, a systematic literature review was undertaken to explore previous approaches aimed at making visual information accessible to blind individuals, both for understanding and creating such content. The primary objective of this study was to categorize the various types of representations, including graphs, diagrams, geometric shapes, maps, and other visual forms utilized in interactions with blind individuals. The methodology adopted consisted of a mixed-method approach, presenting a selection of studies conducted between 2015 and 2023, following a structured protocol for research selection in major academic databases. Consequently, 82 studies were classified according to type of supported tasks, type of representation, sensory modality, and assistive technologies. As a result, an analysis of co-occurrence was presented through a representative network depicting the primary sub-dimensions. Additionally, a matrix of certainties, suppositions, and doubts was constructed, highlighting the state of the art, through the main findings and challenges reported in the selected studies. The expectation is to collaborate with the academic community by showing possibilities among dimensions less addressed in studies with blind individuals in the non-textual context, and then pointing out issues to be addressed in future research.